Comatose With Basilar Artery Occlusion: Still Odds of Favorable Outcome With Recanalization Therapy - Ritvonen, Juhani; Sairanen, Tiina; Silvennoinen, Heli; Virtanen, Pekka; Salonen, Oili; Lindsberg, Perttu J.; Strbian, Daniel (Frontiers in Neurology, 2021)
Background: Around 30–60% of patients with basilar artery occlusion (BAO) present with coma, which is often considered as a hallmark of poor prognosis. Aim: To examine factors that will help predict outcomes in patients with BAO comatose on admission. Methods: A total of 312 patients with angiography-proven BAO were analyzed. Comas were assessed as Glasgow Coma Scale (GCS) of ≤8 or impaired level of consciousness ascertained in the medical records. Outcomes were evaluated with the modified Rankin Scale (mRS) over a phone call at 3 months. In our study, 53 patients were excluded due to inadequate data on the level of consciousness. Results: In total, 103/259 (39.8%) of BAO patients were comatose on admission. Factors associated with acute coma were higher age, coronary artery disease, convulsions, extent of early ischemia by posterior circulation Acute Stroke Prognosis Early CT Score (pc-ASPECTS) < 8, absence of patent posterior collateral vasculature, and occlusion over multiple segments of BA. A total of 21/103 (20.4%) of comatose patients had a favorable outcome (mRS 0–3), and 12/103 (11.7%) had a good outcome (mRS 0–2). Factors associated with a favorable outcome in comatose BAO patients were younger age (p = 0.010), less extensive baseline ischemia (p = 0.027), recanalization (p = 0.013), and avoiding symptomatic intracranial hemorrhage (sICH) (p = 0.038). Factors associated with the poorest outcome or death (mRS 5–6) were older age (p = 0.001), diabetes (p = 0.022), atrial fibrillation (p = 0.016), lower median GCS [4 (IQR 3.6) vs. 6 (5–8); p = 0.006], pc-ASPECTS < 8 (p = 0.003), unsuccessful recanalization (p = 0.006), and sICH (p = 0.010). Futile recanalization (mRS 4–6) was significantly more common in comatose patients (49.4 vs. 18.5%, p < 0.001). Conclusions: One in five BAO patients with acute coma had a favorable outcome. Older patients with cardiovascular comorbidities and already existing ischemic lesions before reperfusion therapies tended to have a poor prognosis, especially if no recanalization is achieved and sICH occurred.